Rancang Bangun Sistem Informasi Fasilitas dan Penunjang Operasional Berbasis Android (Studi Kasus: Bandar Udara Internasional Sam Ratulangi Manado) - Nanda Adhi Winata; Aryo Pinandito; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In an effort to maintain facilities and operational support at Sam Ratulangi International Airport Manado managed by electricity division. In daily tasks, electricity division require conformity about the readiness of device on each shift. Technicians sometimes requires a previous history of damage to help identify damage to the device. This research provide a system capable of distributing data quickly. Almost all technicians have Android devices. Android applications can run in the background and provides data synchronization. Firebase has a feature to trigger updates in real time data and able to send notifications. This research uses an incremental approach to accommodate the user's desire about the system. Begins by analyzing problems that result in functional and non functional requirements. Research continues with the design, system implementation and testing, and system evaluation by stakeholders repeatedly. The design produce system behavior and required data structure. Implementation and testing produce tangible results from system implementation. Stakeholder evaluation generates feedback in subsequent development. The last stage is testing to see if the system capable to solve the problem by comparing the time required. The test results obtained that the business process after implementation faster than before implementation so it is considered to solve existing problems.